Simplify the expression & place the final solution in the a+bi form.
(2 - i)(4 + 2i)
First: eliminate the parenthesis by using the Foil Method.
(2)(4)+ (2)(2i)+ (-i)(4)+ (-i)(2i)
8 + 4i+ (- 4i)+ (- 2i^2)
8 + 4i - 4i - 2i^2
Sec: combine "like" terms.
8 + 0i - 2i^2
8 - 2i^2
Third: the i^2 becomes -1 > replace -1 with i^2
8 - 2(-1)
8 + 2
10
2007-04-11 18:48:00
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
Remember that i^2 = -1 in complex numbers.
(2 - i)(4 + 2i) = 8 - 4i +4i - 2i^2 obtained just multiplying through.
(2 - i)(4 + 2i) = 8 - 2(-1) = 8+ 2 = 10
2007-04-11 17:16:44
·
answer #2
·
answered by Bazz 4
·
0⤊
0⤋
Just multiply it out using FOIL, or the distributive property, or whatever you want to call it.
(2 - i)(4 + 2i) = 8 - 4i + 4i - 2i^2 = 8 - 2i^2
Now, since i^2 = -1, we can further simplify:
8 - 2i^2 = 8 - 2(-1) = 8 + 2 = 10.
So the answer is 10. (or 10 + 0i, if you like).
2007-04-11 17:13:08
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
So this is just like multiplying expressions - use FOIL
8 -4i +4i - 2i^2 =
8 - 2i^2
i^2 = -1, by definition, so
8 + 2
10, or 10 +0i
2007-04-11 17:14:07
·
answer #4
·
answered by John T 6
·
0⤊
0⤋
(2 -i ) (4 +2i)
= 8 -4i + 4i -2i^2
= 8 + 0 -2(-1)
= 8 + 2
= 10
Nota : i^2 = -1
2007-04-11 17:30:05
·
answer #5
·
answered by frank 7
·
0⤊
0⤋
You must distribute.
2*4 + 2*2i - 4i -2i^2
8 + 4i - 4i - (2*-1) , because (i^2 = -1)
8 - -2 = 10
2007-04-11 17:14:57
·
answer #6
·
answered by RonnyJ 3
·
0⤊
0⤋
(2-i)(4+2i)
= 2(4+2i)-i(4+2i)
= 2(4)+2(2i) -i(4)-i(2i)
= 8 + 4i -4i +1(2)
= 8+2
= 10
2007-04-11 17:16:16
·
answer #7
·
answered by chanakya s 1
·
0⤊
0⤋
Again, use FOIL: You get
8 -2i² -4i + 4i= 8+2 = 10.
2007-04-11 17:24:37
·
answer #8
·
answered by steiner1745 7
·
0⤊
0⤋
(2-i)(4+2i): multiply it out just like in algebra
= 2(4) + (-i)(4) + 2(2i) + (-i)(2i)
= 8 + 0i - 2i^2
= 8 + 2
= 10.
2007-04-11 17:12:10
·
answer #9
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
For the first one you've been close, the answer is 14-18i. I were given this by technique of creating use of the FOIL technique, (4+2i)(a million-5i) = 4-20i+2i-10i^2, upload all like words to get 14-18i, out of your answer is sounds like you in elementary words added incorrect. For the 2d one the answer I were given replaced into (9-12i)/5. To get this take the equation (6-3i)/(2+i) and mult. by technique of the complicated conjugate of the denominator so.. (6-3i)/(2+i) * (2-i)/(2-i) by technique of doing this it really is going to eliminate the i words contained in the denominator and provide you with a sparkling complicated huge style contained in the numerator. by technique of doing this I were given (9-12i)/5
2016-12-03 21:27:04
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋